Normal pressure effects upon mechanical properties and microstructure of Ti-6Al-4V and AA2024 rotary friction welds - Lakache Houssem Eddine; May Abdelghani; Badji Riad (Engineering and Applied Science Research, 2023)
The aim of this work is to investigate the effect of normal pressure upon the mechanical properties and their related microstructures of the similar Ti-6Al-4V and AA2024 Rotary Friction Welding (RFW) joints. The main characteristic of this process is the use of friction to generate adequate energy and raise temperature locally in order to create favorable conditions for welding at the interface between two parts. Successful welds were produced showing, among many others, that the fracture occurres at the weld interface for the AA2024 alloy, hence its low tensile strength. However, the fracture occurres outside the weld interface for the Ti-6Al-4V alloy, which indicates that the weld joint is more resistant than the base metal. The microscopic observation of the fracture surfaces of the AA2024 samples exhibits a mixture of morphologies with a majority of rough cupular surfaces, indicating a dominant ductile fracture mode. For the Ti-6Al-4V RFW joints, cupules of different sizes are observed over the entire surface that also exhibits a ductile fracture mode.